Performance evaluation of a water ejection type in vacuum drying system - Pipatpong Watanawanyoo (2018)
This research was to study the possibility of applying a vacuum drying system operated by water ejector pump to dry agricultural product commercially. The objective aimed to examine the impact of some variables on water ejector pump's performance and predict the best point for drying. The effect of four dependent variables, i.e. vacuum, temperature, water pressure and make-up air quantity on the moisture removal in a drying chamber was studied. The performances of a water injection vacuum drying system, the forms of moisture extraction ratio (MER) and specific moisture extraction ratio (SMER) were evaluated at the steady state (or constant drying rate) of water in a tray-dryer chamber. Four values of the vacuum in the range of 17 kPa (-60 cmHg) to atmospheric pressure (0 cmHg) combined with four values of temperature setting in the range of 40 to 70°C, were used. The result revealed that the air temperature was the most influential effect on the MER and SMER compared to the vacuum pressure in the chamber. The vacuum pressure offered the least effect to the MER and SMER of the system. However, breeding the fresh air into the chamber while retaining the preset value of vacuum increased the MER and SMER. The MER and SMER at the chamber's temperature of 50, 60, 70°C when compared to the values at 40°C, were increased about 50, 120, 200% and by 40, 100, 150% respectively. With reference to the values of MER and SMER at the vacuum pressure of 17 kPa (-60 cmHg), it was found that at 44 kPa (-40 cmHg) and 70 kPa (-20 cmHg), the MER decreased by 8 and 7% respectively. In contrary to the same reference vacuum pressure of 17 kPa (-60 cmHg), the SMER, at 44 kPa (-40 cmHg) and 70 kPa (-20 cmHg) were increased by 7 and 3%, respectively. © 2014 Published by Elsevier Ltd.